Pharmacokinetics of tolfenamic acid in goats after different administration routes - Turk, Erdinc; Tekeli, Ibrahim Ozan; Durna Corum, Duygu; Corum, Orhan; Altinok Yipel, Fulya; Ilhan, Aysun; Emiroglu, Sara Busra; Uguz, Halis; Uney, Kamil (Wiley, 2021)
AbstractThe aim of this study was to determine the pharmacokinetics and bioavailability of tolfenamic acid in goats after intravenous (IV), intramuscular (IM), subcutaneous (SC), and oral (PO) administrations at 2 mg/kg dose. In this study, eight clinically healthy goats were used. The study comprised four periods, according to a crossover design with at least a 15‐day washout period between treatments. Plasma concentrations of tolfenamic acid were determined by HPLC‐UV, and the pharmacokinetic parameters were estimated using a non‐compartmental method. Following IV administration, terminal elimination half‐life, volume of distribution at steady state, and total clearance were 1.60 h, 0.37 L/kg, and 0.27 L/h/kg, respectively. The mean peak plasma concentration following IM, SC, and PO administrations was 1.77, 1.22, and 0.30 μg/ml, respectively. The mean bioavailability following IM, SC, and PO administrations was 64.46, 55.43, and 19.46%, respectively. The PO route, which exhibits both the low plasma concentration and bioavailability, is not recommended in goats. The IV, IM, and SC routes, which show comparable pharmacokinetic profiles, may be proposed for use in goats. However, the multi‐dose and pharmacodynamic studies are necessary to establish more accurately its safety and efficacy in the goat.
Keywords: Area Under Curve; Goats; Animals; ortho-Aminobenzoates; Half-Life; 2. Zero hunger; 3. Good health